(untitled) (Journal of Engineering, 2014)
The research shed light on the historic evolution of Baghdad through its long, expansive history. The starting point focuses on the geographic characteristics, and the nature of its habitation, prior to laying the circular plan of Baghdad. Then the research proceeds to cover the stage of building the round city of Baghdad. The research continue to cover the expansion and sequential growth across the banks of Tigris river. A concentrated attention is devoted to analyses the morphological, geographical and above all the makeup of present day city of Baghdad, pinpointing the apathetic plans, decisions, and actions which completely disfigured the image, and tradition of the old city of Baghdad, behind the delusive slogans of “comprehensive development”. From the above ejective acts, the research problem is formulated as: The gradual dilapidation of major components that recall the historic image of Baghdad. The research assumption thus formulated the causes that lead to the disfigurement of Baghdad historic identity in the consequent plans and policies which gave little or no attention to the historic developmental formation of the city. From the above assumption, the research goal can be stated as “Pin pointing the historic path of development to enclose the salient historic features that makes impact on the present day image of Baghdad.